Amaranth as a Source of Antihypertensive Peptides - Nardo, Agustina E.; Suárez, Santiago; Quiroga, Alejandra V.; Añón, María Cristina (Frontiers in Plant Science, 2020)
Numerous studies have shown that amaranth storage proteins possess encrypted sequences that, once released, exhibit different physiological activities. One of the most studied is antihypertensive activity. This review summarizes the progress made in a little over a decade (2008-2020) related to this topic. Amaranth is an ancestral crop used by pre-Columbian cultures for 6000-8000 years. Its grains have a relevant chemical composition not only from a nutritional point of view but also due to the contribution of components with good techno-functional properties and important potential as bioactive compounds. Studies related to inhibition of different enzymes of the Renin-Angiotensin-Aldosterone system, in particular ACE and Renin, as well as those referring to potential modulation mechanisms of tissue or local Renin-Angiotensin-Aldosterone system, are analyzed, including in silico, in vitro, in vivo and ex vivo assays. Furthermore, the potential use of these bioactive peptides or products containing them, in the elaboration of functional food matrices is discussed. Finally, the most relevant conclusions and future requirements in research and development of food products are presented.